2020
DOI: 10.1186/s41544-020-00052-3
|View full text |Cite
|
Sign up to set email alerts
|

Systemic spreading of exogenous applied RNA biopesticides in the crop plant Hordeum vulgare

Abstract: Background: Small (s) RNA molecules are crucial factors in the communication between hosts and their interacting pathogens/pests that can modulate both host defense and microbial virulence/pathogenicity known as crosskingdom RNA interference (ckRNAi). Consistent with this, sRNAs and their double-stranded (ds) RNA precursors have been adopted to control plant diseases through exogenously applied RNA biopesticides, known as spray-induced gene silencing (SIGS). While RNA spray proved to be effective, the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 49 publications
0
53
0
Order By: Relevance
“…Another study supported these findings, showing that exogenously applied dsRNA derived from the HC-Pro and CP genes of ZYMV protects watermelon and cucumber against ZYMV and that it spread systemically over long distances in cucurbits (Kaldis et al, 2018). Further emphasizing the systemic spread of RNA biopesticides, the movement of sprayed dsRNA from barley leaves to stems and root tissues was demonstrated within 3 days after spray treatment (Biedenkopf et al, 2020). Systemic distribution is of key importance because it indicates that RNA biopesticides could be promising substitutes for systemic pesticides.…”
Section: Major Challenges and Recent Achievements In Transferring Rna Spray To Field Environmentsmentioning
confidence: 72%
See 1 more Smart Citation
“…Another study supported these findings, showing that exogenously applied dsRNA derived from the HC-Pro and CP genes of ZYMV protects watermelon and cucumber against ZYMV and that it spread systemically over long distances in cucurbits (Kaldis et al, 2018). Further emphasizing the systemic spread of RNA biopesticides, the movement of sprayed dsRNA from barley leaves to stems and root tissues was demonstrated within 3 days after spray treatment (Biedenkopf et al, 2020). Systemic distribution is of key importance because it indicates that RNA biopesticides could be promising substitutes for systemic pesticides.…”
Section: Major Challenges and Recent Achievements In Transferring Rna Spray To Field Environmentsmentioning
confidence: 72%
“…Thus, knowledge of the paths used by dsRNA and siRNA as SIGS inducers is a prerequisite for further developing and applying RNA sprays to the field. Given this assumption, previous reports revealed the systemic spread of sprayed RNAs (Koch et al, 2016;Konakalla et al, 2016;Kaldis et al, 2018;Biedenkopf et al, 2020). Spraying a fluorescent-labeled dsRNA onto barley leaves and subsequently examining longitudinal leaf sections revealed that the fluorescence was not confined to the apoplast but also was present in the symplast of phloem parenchyma cells, companion cells and mesophyll cells, as well as in trichomes and stomata (Koch et al, 2016).…”
Section: Significant Advances Of Rna Spray Controlling: Insectsmentioning
confidence: 99%
“…The analogous disease severity of the pathogen observed in the second experiment both on the leaves that were directly treated with dsRNA and those directly above the treated leaves (systemic diffusion), which was significantly lower than that achieved in the water-treated samples, indicates the presence of a systemic effect of the treatment that should be more deeply investigated in future studies. Systemic RNAi has been observed in other plants, such as A. thaliana ( Melnyk et al, 2011 ), Hordeum vulgare ( Biedenkopf et al, 2020 ), and Nicotiana benthamiana ( Chen et al, 2018 ), but to the best of our knowledge, no information is reported for grapevine.…”
Section: Discussionmentioning
confidence: 99%
“…Aphids possess functional RNAi machinery and have been shown to respond to environmental RNAi with diffusion of the silencing signal to the whole insect body (systemic RNAi and cell‐autonomous RNAi) (Wang et al ., 2015). However, aphids require phloem sap for nutrition; therefore the nature of the HIGS trigger relies mainly on siRNA uptake (Biedenkopf et al ., 2020) as HIGS‐introduced dsRNA will be processed into siRNAs by the plant RNAi machinery. Therefore, the quantity and quality (target gene accessibility) of phloem‐mediated siRNA uptake are important determinants of HIGS efficacy in controlling aphids.…”
Section: Uptake Mechanism: Dsrna Vs Sirnamentioning
confidence: 99%